2020
DOI: 10.1002/cad.20361
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and peer support for aggression and delinquency during adolescence in nine countries

Abstract: This study tested culture-general and culturespecific aspects of adolescent developmental processes by focusing on opportunities and peer support for aggressive and delinquent behavior, which could help account for cultural similarities and differences in problem behavior during adolescence. Adolescents from 12 cultural groups in 9 countries (China, Colombia, Italy, Jordan, Kenya, the Philippines, Sweden, Thailand, and the United States) provided data at ages 12, 14, and 15. Variance in opportunities and peer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Similar to both Cho et al's (2005) and Dishion et al's (2001) results, the findings from this study revealed that by aggregating students with similar backgrounds and behavioural challenges, there was an increase and enhancement of deviant and disruptive behaviours. These findings are similar to those reported in the literature on 'deviancy training' and deviant peer contagion (Dishion et al, 1999;Lansford et al, 2020), in that, TACKLE provided disengaged students with the opportunity to socialise with other deviant peers. Consequently, it became a setting that was conducive to the development of deviant behaviours and resulted in a perception between students that such behaviours were desirable and the norm.…”
Section: Discussion: How Did Tackle Work For Whom and Under Which Circumstances?supporting
confidence: 88%
See 3 more Smart Citations
“…Similar to both Cho et al's (2005) and Dishion et al's (2001) results, the findings from this study revealed that by aggregating students with similar backgrounds and behavioural challenges, there was an increase and enhancement of deviant and disruptive behaviours. These findings are similar to those reported in the literature on 'deviancy training' and deviant peer contagion (Dishion et al, 1999;Lansford et al, 2020), in that, TACKLE provided disengaged students with the opportunity to socialise with other deviant peers. Consequently, it became a setting that was conducive to the development of deviant behaviours and resulted in a perception between students that such behaviours were desirable and the norm.…”
Section: Discussion: How Did Tackle Work For Whom and Under Which Circumstances?supporting
confidence: 88%
“…These findings can be interpreted within dual systems theory (Steinberg, 2008;. Specifically, this theory suggests that the parts of the brain that respond to rewards develop during early adolescence (i.e., aged 10 -14 years old) (Lansford et al, 2020). In contrast, the parts of the brain that are responsible for response inhibition, cognitive, and behavioural control develop gradually throughout adolescence and early adulthood (Casey, Heller, Gee, & Cohen, 2019;Cohen et al, 2016;Steinberg, 2008).…”
Section: Discussion: How Did Tackle Work For Whom and Under Which Circumstances?mentioning
confidence: 90%
See 2 more Smart Citations
“…Karataş et al (2020) present, and comparatively discuss, two empirical studies conducted in two independent cultural contexts that sought to understand acculturation orientations of adolescents from migrant families, according to their parents own acculturation orientations and classmates' acculturation preferences. Lansford et al (2020) illustrate the benefits of embedding the study of development within cultural contexts through large-scale international collaborative research. They report on an empirical study among 12 cultural groups of adolescents that highlights culture-general and culture-specific aspects of adolescent developmental processes and risk for aggression and delinquency.…”
Section: Transition and Developmentmentioning
confidence: 99%